Immunoglobulin light chain mRNA is processed from large nuclear RNA. - Gilmore-Hebert, M (1978)
Recombinant DNA probes, produced by the molecular cloning of immunoglobulin kappa light chain mRNA, have been used to analyze heterogenous nuclear RNA for presumptive precursors to cytoplasmic kappa light chain mRNA, Three discrete classes of nuclear RNA containing kappa mRNA sequences were detected after pulse-labeling of immunoglobulin-producing P3 myeloma cells. Two of these were substantially larger than kappa mRNA (approximately 10 and 4 times larger); the third was similar in size to kappa mRNA. Beginning with the largest, the sequential appearance of these three classes of nuclear RNA preceded the first appearance of newly synthesized kappa light chain mRNA in the cytoplasm. The results presented here suggest that immunoglobulin kappa light chain mRNA is generated by the stepwise cleavage and processing of a large nuclear RNA transcript.